Symptomatology and allergen types in patients presenting with allergic rhinitis (Bangladesh Journal of Otorhinolaryngology, 2012)
Allergic rhinitis, despite its complex patho-physiology, is a global health problem with the increasing prevalence. The current study which was conducted at one of the tertiary care center in the country comprised of 548 diagnosed cases of allergic rhinitis and thus treated during the period extending from January 2010 to June 2011. In the study, males and females were almost equally distributed, constituting the ratio of 1:0.9. Among them, the patients from 20 29 year of age group was the most commonly affected (38.1%). In our study most of the patients were housewives (30.3%) and the house dusts mites (76.3%), was the most common etiological factors. Majority of the patients presented with sneezing (86.7%) as the chief complaint. Of the total subjects, 18.6% presented with co-morbidity of allergic conjunctivitis and 8.9% with that of sinusitis. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10411  Bangladesh J Otorhinolaryngol 2012; 18(1): 30-35